Vito Acconci : the city inside us. - Acconci, Vito; Noever, Peter; Prince, Richard; Vidler, Anthony; Exhibition. Vito Acconci : the city inside us. MAK (Österreichisches Museum für angewandte Kunst / Gegenwartskunst) Wien. 1993-03-17. 1993-08-29 (Wien : MAK (Österreichisches Museum für angewandte Kunst / Gegenwartskunst) Wien, 1993)
In the central exhibition hall of the Austrian Museum of Applied Arts in Vienna, Vito Acconci, one of the most unconventional and versatile artists of our days, has created a room installation extraordinary in both its dimensions and message, the present catalogue documents this temporary work of art and also presents a selection of Acconci's works between 1976 to 1992, together with essays and explanatory texts by the artist.
bibliog. p. 191-192
biog., ind. tent., gr. tent., projecten p. 184-190
Duits
Engels
boek
Keywords: Acconci, Vito